Effects of Gluconacetobacter xylinus Concentrations on the Physicochemical Properties of Bacterial Cellulose from Coconut Water Medium - Yunan Kholifatuddin Sya'di; Damar Bima Wicaksono; Agus Suyanto (The University of Lampung, 2025)
Utilization of coconut water into a bacterial cellulose product is promising to take advantage of the abundant natural resources. The synthesis of bacterial cellulose using coconut water media requires optimal conditions to achieve the best characteristics as a bioplastic component. This study aims to determine the effect of variations in the concentration of Gluconacetobacter xylinus starter. The type of research is experimental using a one-factor Complete Random Design (RAL) by going through a fermentation process influenced by variations in starter concentrations (5%, 7%, 9%, 11%, 13%, 15%) with test parameters including water vapor permeability, tensile strength, and crystallinity index. The results showed a significant influence (p≤0.05) of water vapor permeability testing, tensile strength testing, and yield testing. The crystallinity index test of the best treatment obtained a concentration of 15%. The best treatment of 15% resulted in the average water vapor permeability (3.84x10-7 g/(m2/day)), tensile strength (69.25 MPa), crystallinity index (91.35%), and yield (75.70%). Bacterial cellulose produced using a 15% starter can be used as bioplastic packaging material and allows for further research by combining it with other materials to obtain the best and most affordable bioplastic formulation.